S55 Effect of electronic cigarette extraction on vasoactive gene expression in human pulmonary artery smooth muscle and endothelial cells. (December 2018) - Alqarni, A; Brand, O; Alice, P; Alshehri, M; Pang, L
Abstract : Introduction: Pulmonary Hypertension (PH) is a common and serious complication of COPD. We previously demonstrated that Cigarette Smoke Extracts (CSE) induced imbalanced vasoactive gene expression in human Pulmonary Artery Smooth Muscle Cells (hPASMCs) and Pulmonary Artery Endothelial Cells (hPAECs). Although increasing evidence shows that electronic cigarette (e-cigarette) containing nicotine is associated with increased risk of cardiovascular disease, the effect of e-cigarette vapour extracts (ECVE) on vasoactive gene expression in hPASMCs and hPAECs is unknown. We hypothesize that ECVE may have similar effects as CSE on the induction of an imbalance between excessive vasoconstrictors and deficient vasodilators, which then contributes to aberrant hPASMC proliferation in COPD-associated PH. Methods: ECVE was prepared the same way as CSE from 6 ml e-cigarette liquid with and without nicotine (0.24 mg/ml nicotine, total nicotine the same as two cigarettes used for CSE). Confluent hPASMCs and hPAECs were treated with different concentrations of ECVE. Western blotting and real-time RT-PCR were used to assess protein and mRNA expression of Prostacyclin Synthase (PGIS), and Cyclooxygenase-2 (COX-2), Endothelial Nitric Oxide Synthase (eNOS), Thromboxane A Synthase (TXAS), Endothelin 1(ET-1), respectively. Results: PGIS protein was markedly reduced by ECVE with and without nicotine in a concentration-dependent manner in hPASMCs. However, ECVE had no effect on the protein of PGIS in hPAECs and mRNA expression of PGIS in both hPASMCs and hPAECs. ECVE with and without nicotine had no effect on the protein and mRNA expression of eNOS, COX-2, and TXAS in both hPASMCs and hPAECs. Although ECVE had no effect on ET-1 mRNA in hPAECs, the mRNA expression of ET-1 was significantly downregulated by ECVE with nicotine. Conclusion: Although ECVE had no similar effects on imbalanced vasoactive gene expression as CSE, ECVE reduced the PGIS protein and ET-1 mRNA in hPASMCs, which then could contribute to aberrant hPASMC proliferation in COPD-associated PH. Further studies will be conducted to measure the mediator releases of NO, PGI2, TXA2, PGE2, and ET-1 to confirm the effects of ECVE.